On the summability of the spectral expansions associated with the elliptic differential operators - Rakhimov, Abdumalik (IOP Publishing Ltd., 2018)
In this paper we study the summability problems of the spectral expansions associated with the elliptic partial differential operators in the spaces of distributions. In particular, the problems studied for the Schrodinger operator with the singular potential. For this operator theorems on the summability of the Fourier expansions in the generalised Holder spaces and in the Sobolev spaces of the mixed norm proved. The conditions obtained are accurate in the classes of considered distributions.